Design and evaluation of the FAMILIAR tool - Jaksic, Aleksandar, author; France, Robert B., advisor; Anderson, Charles W., committee member; Ghosh, Sudipto, committee member; Troup, Lucy J., committee member (Colorado State University. Libraries, 2014)
Software Product Line Engineering (SPLE) aims to efficiently produce multiple software products, on a large scale, that share a common set of core development features. Feature Modeling is a popular SPLE technique used to describe variability in a product family. FAMILIAR (FeAture Model scrIpt Language for manipulation and Automatic Reasoning) is a Domain-Specific Modeling Language (DSML) for manipulating Feature Models (FMs). One of the strengths of the FAMILIAR language is that it provides rich semantics for FM composition operators (aggregate, merge, insert) as well as decomposition operators (slice). The main contribution of this thesis is to provide an integrated graphical modeling environment that significantly improves upon the initial FAMILIAR framework that was text-based and consisted of loosely coupled parts. As part of this thesis we designed and implemented a new FAMILIAR Tool that provides (1) a fast rendering framework for the graphically representing feature models, (2) a configuration editor and (3) persistence of feature models. Furthermore, we evaluated the usability of our new FAMILIAR Tool by performing a small experiment primarily focusing on assessing quality aspects of newly authored FMs as well as user effectiveness and efficiency.
Keywords: feature models; feature modeling; FAMILIAR; FAMILIAR tool; software product lines